Efficient fast motion estimation algorithm for real-time applications - Agha, Shahrukh; Khan, Mansoor; Jan, Farmanullah (Journal of real-time image processing, 2022)
Motion estimation (ME) process is the most computational complex part of a video encoder. It exploits temporal redundancy present in a video sequence to achieve compression. To make the video encoding process in real time, alleviating the computational burden of motion estimation is mandatory. In this work, an efficient hierarchical diamond search (EHDS) ME algorithm is being presented. This algorithm consists of multiresolution hierarchies, modified diamond search and modified early jump-out mechanism. Multiresolution hierarchies and the modified diamond search algorithm help either locate the global minima or some location nearby it, as best match by first finding starting point of search near the global minima which improves quality and reduces complexity, while the modified early jump-out mechanism further reduces complexity. Results have shown that the proposed algorithm has less complexity and power consumption than the conventional diamond search (DS) and other existing DS algorithms, while the quality is comparable to full search (FS) ME algorithm.